Potential for Budget Disharmonization in the Management of the Merah Putih Village Cooperative - Adnan Hasanudin; Atik Winanti; Aurora Jilena Meliala (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research aims to determine whether the budget formulation of the Merah Putih Village Cooperative is in accordance with the norms and statutory regulations as stipulated in Law Number 25 of 1992 concerning Cooperatives, particularly in relation to Article 33 paragraph (4) of the 1945 Constitution, which emphasizes the principle of independence in the national economy. The results of this study focus on optimizing the establishment of the Merah Putih Village Cooperative to support the formation of national-scale cooperatives that function not only as savings and loan institutions driving the economy, but also address the challenges and risks that may arise from the establishment of the Merah Putih Cooperative. First, the issue of economic scale is crucial. Operations at the village level are often limited by available resources and market reach. Second, human resource capacity is a determining factor. The management of funds amounting to IDR 3–5 billion requires financial, business, operational, and marketing management skills that are not always present in every village. Experience with Village-Owned Enterprises (BUMDes) shows that one of their main challenges is finding local residents who are truly skilled managers. Third, elite capture or control by local elites can become a bottleneck. In villages with weak governance, influential figures may abuse their authority to control the cooperative for personal gain. Similar occurrences are often found in grant programs from Ministries/Agencies or the private sector, where key individuals dominate and exploit these resources for their own interests. Fourth, the risk of fraud.